Association of British Clinical Diabetologists (ABCD) and Diabetes UK joint position statement and recommendations for non-diabetes specialists on the use of sodium glucose co-transporter 2 inhibitors in people with type 2 diabetes (January 2021). Issue 3 (2021) - Dashora, Umesh; Gregory, Robert; Winocour, Peter; Dhatariya, Ketan; Rowles, Susannah; Macklin, Andrew
No abstract available